Temporal dynamics, climate associations, and surveillance performance of Lassa fever in Nigeria, 2020–2025: a national longitudinal analysis - Ayokunle John Tadema; Faith Mmesoma Nwosu; Oluwatumilara Ayokunle Abimbola (Osong Public Health and Research Perspectives, 2026)
Objectives: We examined national temporal trends, laboratory-confirmation performance, and climate associations in Lassa fever surveillance in Nigeria from 2020 to 2025, and assessed the impact of the coronavirus disease 2019 (COVID-19) pandemic on surveillance metrics. Methods: We analyzed 307 consecutive weeks of national Lassa fever surveillance data using an ecological study design. Primary outcomes included confirmed-case counts, case fatality rate (CFR), and laboratory-confirmation rate (LCR). Temporal trends were evaluated using regression models, climate associations using correlation and negative binomial regression analyses, and the impact of COVID-19 using interrupted time-series analysis. Results: Overall, 47,029 suspected cases, 6,288 confirmed cases, and 975 deaths were reported. The mean LCR was 11.2% (standard deviation, 7.2%), declining from 18.4% in 2020 to 9.9% in 2025 (p